ANALISIS YURIDIS PERTANGGUNG JAWABAN BARANG SITAAN ATAS HASIL TINDAK PIDANA NARKOTIKA (STUDI PENELITIAN DI KEJAKSAAN NEGERI BATAM) - Citra Aulia Sari; Juhrin Pasaribu; Ramlan Ramlan (Ensiklopedia of Journal, 2023)
Handling of Narcotics Crimes has become the concern of many parties, both from within and outside the country, so that the handling of Narcotics Crime cases includes the handling of the evidence must be carried out professionally and with integrity. This study aims to determine the legal arrangements as well as what are the obstacle factors in the Liability for Confiscated Goods for the Proceeds of Narcotics Crimes. This research uses empirical legal research (field) and normative law (library) by using research methods consisting of two forms, namely normative legal research or doctrine and empirical or sociological legal research using normative juridical approaches, namely in the form of analysis of the articles that regulate things that become problems to obtain secondary data and sociological juridical approach to obtain primary data through field research. The results in this study indicate that (1) the legal arrangements in Liability for Confiscated Goods for the Results of Narcotics Actions (Research Studies at the Batam District Attorney) have been carried out well as a supporter of accountability in proving the equipment of letters and files of confiscated goods in the Narcotics Crime. (2) Implementation, and obstacle factors as well as solutions for Liability for Confiscated Goods for the Results of Narcotics Crime (Research Study at the Batam District Attorney) confiscated goods are not immediately stored in the State Confiscated Property House. Instead, they will be brought to the District Attorney's Office for the adjustment of administrative completeness and the authenticity of the confiscated objects. The Prosecutor's Office in the responsibility of completing data and files for determining the status of confiscated goods requires good handling and cooperation with each investigator from several agencies.